Impact of bile salt adaptation of Lactobacillus delbrueckii subsp. lactis 200 on its interaction capacity with the gut - Burns, Patricia Graciela (2011)
In a previous work, bile-salt-resistant derivatives were obtained from non-intestinal lactobacilli. The aim of this work was to investigate the impact of bile adaptation of Lactobacillus delbrueckii subsp. lactis 200 on morphology, surface properties, in vivo interaction capacity with the gut and ability to activate the gut immune response. Electron microscopy studies, growth kinetics in the presence of bovine and porcine bile, the capacity to deconjugate bile acids, hydrophobicity, autoaggregation and co-aggregation capacities were studied for the parental strain and its bile-resistant derivative in vitro. Additionally, survival in intestinal fluid, the interaction with the gut and the immunomodulating capacities were studied in mice. Bile salt adaptation conferred upon the adapted strain a higher capacity to withstand physiological concentrations of bile salts and greater survival capacity in intestinal fluid. However, bile salt exposure reduced cell hydrophobicity, autoaggregation and adhesion capacities, resulting in reduced persistence in the intestinal lumen and delayed capacity to activate the gut immune response. Insight into the effects of bile salts upon the interaction and immunomodulating capacity of lactobacilli with the gut is provided, relating in vitro and in vivo results. © 2011 Institut Pasteur.